Squaring the speed of light? Regulating market access in algorithmic finance. Issue 2 (2nd April 2016) - Lenglet, Marc; Mol, Joeri
Abstract: We examine the sociomaterial regulation of algorithmic trading against the background of the European Union's directives on Markets in Financial Instruments (MiFID/MiFIR). Tracing the purification and translation of regulatory practices within a French brokerage firm, we examine the impact of electronic trading on the nature of market access. Central to our analysis is the 'Blackbox', a tool designed to manage market access efficiently by collating trade flows and automatically pairing them with trading algorithms. Our findings show that, through a process of 'abstracting', purification and translation are kept strictly separate, allowing the broker to meet the regulatory requirements de jure whilst retaining de facto the unregulated advantages of high-speed materiality. We discuss the implications for both the policy and practice of high-speed financial trading.